Cost-effectiveness analysis of a quantitative immunochemical test for colorectal cancer screening - Wilschut, J.; Hol, L.; Dekker, E.; Jansen, J.; Van Leerdam, M.; Lansdorp_Vogelaar, Iris; Kuipers, E.; Habbema, J.; Van Ballegooijen, M. (W.B. Saunders Co., 2011)
Background & Aims: Two European randomized trials (N = 30,000) compared guaiac fecal occult blood testing with quantitative fecal immunochemical testing (FIT) and showed better attendance rates and test characteristics for FIT. We aimed to identify the most cost-effective FIT cutoff level for referral to colonoscopy based on data from these trials and allowing for differences in screening ages. Methods: We used the validated MIcrosimulation SCreening ANalysis (MISCAN)-Colon microsimulation model to estimate costs and effects of different screening strategies for FIT cutoff levels of 50, 75, 100, 150, and 200 ng/mL hemoglobin. For each cutoff level, screening strategies were assessed with various age ranges and screening intervals. We assumed sufficient colonoscopy capacity for all strategies. Results: At all cost levels, FIT screening was most effective with the 50 ng/mL cutoff level. The incremental cost-effectiveness ratio of biennial screening between ages 55 and 75 years using FIT at 50 ng/mL, for example, was 3900 euro per life year gained. Annual screening had an incremental cost-effectiveness ratio of 14,900 euro per life year gained, in combination with a wider age range (between ages 45 and 80 years). In the sensitivity analysis, 50 ng/mL remained the preferred cutoff level. Conclusions: FIT screening is more cost-effective at a cutoff level of 50 ng/mL than at higher cutoff levels. This supports the recommendation to use FIT at a cutoff level of 50 ng/mL, which is considerably lower than the values used in current practice. © 2011 AGA Institute.